High resolution mapping DNAs by R-loop atomic force microscopy. - Klinov, D V (1998)
R-loops formed by short RNA transcripts have been imaged by atomic force microscopy (AFM) at a constant force in the height mode. The technique was applied to mapping the human endogenous retrovirus K10 family (HERV-K10) long terminal repeats (LTR) within individual plasmids and cosmids. RNA probes specific for the U3 (384 nt) and U5 (375 nt) LTR regions separated by a span of 200 bp were used for R-loop formation with LTRs located within plasmid (3.8 kb) or cosmid ( approximately 40 kb) DNAs. R-loops stabilized by glyoxal treatment and adsorbed onto the mica surface in the presence of magnesium ions looked like looped out segments of RNA:DNA hybrids. The total yield of R-loops was usually approximately 95%. The RNA:DNA hybrids were found to be 12-15% shorter than the corresponding DNA:DNA duplex. The two regions of the LTR could be easily discerned in the AFM images as clearly separated loops. R-loop positions determined on cosmids by AFM were accurate to approximately 0.5% of the cosmid length. This technique might be easily adapted for mapping various sequences such as gene exons or regulatory regions and for detecting insertions, deletions and rearrangements that cause human genetic diseases.